Dinitrogen Activation by a Titanium/Ruthenium Heteromultimetallic Hydride Complex - Shima, Takanori; Hou, Zhaomin (European journal of inorganic chemistry, 2020)
A titanium/ruthenium heteromultimetallic polyhydride complex [(Cp'Ti)2(Cp*Ru)2(µ‐H)6] (3) (Cp' = C5Me4SiMe3, Cp* = C5Me5) was obtained from the reaction of [Cp'Ti(CH2SiMe3)3] (1) with [Cp*Ru(µ‐H)4RuCp*] (2) under H2. Complex 3 can readily react with N2 to give an imido/nitrido complex [(Cp'Ti)2(Cp*Ru)2(µ‐NH)(µ‐N)(µ‐H)3] (4) via N–N bond cleavage and N–H bond formation. The result demonstrates that the heteromultimetallic hydride complexes can serve as a platform for dinitrogen activation. Reaction of the titanium alkyl complex with the dinuclear ruthenium hydride complex under H2 afforded a Ti/Ru heteromultimetallic hydride complex, which can react with N2 to give a nitrido/imido complex through the cleavage and partial hydrogenation of N2.